Программное обеспечение для оптимизации конструкции механизмов по критерию относительной износостойкости - Шашко, А. Е.; Авсиевич, А. М.; Пронкевич, С. А. (БНТУ, 2014)
The paper describes the algorithm for calculating the distribution of the contact pressure and relative wear resistance criteria on the surface of rotation kinematic pairs. The product of contact pressure on each surface element at relative sliding velocity is selected as the criteria of relative wear resistance of the elementary parts of the surfaces. It is established that for internal combustion engine the decrease of the load and the relative wear on the crank pin of the crankshaft takes place with increasing distance from the axis of the collar to the center of mass of the rod. Developed software makes possible to predict the resource and the energy consumption of different design options designed machines and optimize its design. Proposed approach can be applied to study the loading of kinematic pairs for different types of mechanisms.